2011
DOI: 10.1590/s2236-89062011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Abundância e biomassa de lianas em um fragmento de floresta Atlântica

Abstract: -(Liana abundance and biomass in an Atlantic forest fragment). Lianas represent an important component of the structure and diversity of tropical forests. Normally, in disturbed forest a higher density and biomass of lianas is found compared with undisturbed forests. The aim of this study was to evaluate if the abundance and biomass of lianas differ between bamboo-dominated and non-dominated areas in Parque Estadual das Fontes do Ipiranga. Sample plots of 0.7 ha were established in both areas, and a standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
1
0
6
Order By: Relevance
“…Consequently, Area 1 has been without severe anthropic disturbances for at least 64 years, although it is just 150 m from the park perimeter (east boundary with Cursino Avenue). This low level of perturbation has been corroborated by recent studies on nutrient cycling (Moraes 2002;Santos 2014;Bazi & Gomes 2015;2016;Vieira 2015) and plant community dynamics (Davison 2006;Carvalho et al 2011;Kondrat 2014). The road Alameda Von Martius, which belongs to the Botanical Garden (JBSP), an administrative unit inside PEFI, borders Area 2.…”
Section: Field Proceduressupporting
confidence: 59%
“…Consequently, Area 1 has been without severe anthropic disturbances for at least 64 years, although it is just 150 m from the park perimeter (east boundary with Cursino Avenue). This low level of perturbation has been corroborated by recent studies on nutrient cycling (Moraes 2002;Santos 2014;Bazi & Gomes 2015;2016;Vieira 2015) and plant community dynamics (Davison 2006;Carvalho et al 2011;Kondrat 2014). The road Alameda Von Martius, which belongs to the Botanical Garden (JBSP), an administrative unit inside PEFI, borders Area 2.…”
Section: Field Proceduressupporting
confidence: 59%
“…In early successional stages it is common to find higher abundance of lianas with smaller diameters (Dewalt et al, 2000;Medeiros and Torezan, 2013). Carvalho et al (2011) highlighted that, usually, lianas with large diameters are found mostly in areas with low levels of disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…ha -1 ). A maior abundância de lianas de diâmetro pequeno e uma abundância relativamente baixa para classes de lianas de maior porte no fragmento de Cerrado estudado seguem um padrão comum encontrado em estudos realizados em florestas tropicais van MELIS, 2008;CARVALHO et al, 2011;NOGUEIRA et al, 2010;ALVES et al, 2012). Quando as lianas se tornam grandes, a estrutura física e a disponibilidade de suporte passam a ter grande importância na determinação dos modelos de variação de abundância (NOGUEIRA et al, 2010).…”
Section: Discussionunclassified